Angular Distortion Removal of THz Anisotropic Dichroism Microscope - Y. Deng; K. Niessen; A. Markelz (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We have developed a stationary sample THz anisotropic dichroism microscope as a powerful tool for material characterization. The key innovation is the use of an iso-response curve defined by the terahertz and detection light polarizations. Here we show that following a continuous iso-response curve introduces angular distortion in the spectrum, and this distortion can be eliminated by using a discontinuous iso-response angle pairs avoiding large gradient regions. Employing this additional constraint on the relative polarizations provides a convenient technique for rapid anisotropic terahertz spectroscopy.
Keywords: absorption; angular distortion removal; Biomedical measurement; continuous iso-response curve; detection light polarizations; discontinuous iso-response angle pairs; Distortion; light polarisation; material characterization; Microscopy; proteins; rapid anisotropic terahertz spectroscopy; relative polarizations; spectroscopy; stationary sample; terahertz spectroscopy; terahertz wave spectra; THz anisotropic dichroism microscope; vibrations